2011
DOI: 10.1007/s11064-011-0592-1
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-, IGF-1- and GDNF-Secreting Human Neural Progenitor Cells Rescue Amyloid β-Induced Toxicity in Cultured Rat Septal Neurons

Abstract: Alzheimer's disease (AD) is characterized by the depositions of amyloid-β (Aβ) proteins, resulting in a reduction of choline acetyltransferase (ChAT) activity of AD brain in the early stages of the disease. Several growth factors, including brain-derived neurotrophic factor (BDNF), insulin-like growth factor (IGF)-1 and glial cell-derived neurotrophic factor (GDNF) are known to protect neuronal cell death in several neurodegenerative both in vitro and in vivo models. In this study, septal neurons were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…30 In neuronal cultures, BDNF has specific and dose-dependent protective effects on neuronal toxicity induced by Ab 1-42 and Ab [25][26][27][28][29][30][31][32][33][34][35] . It can completely reverse the toxic action induced by Ab 1-42 and partially by Ab [25][26][27][28][29][30][31][32][33][34][35] . These effects involve TrkB receptor activation since the effect is inhibited by K252a.…”
Section: Bdnf/trkb and Abmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In neuronal cultures, BDNF has specific and dose-dependent protective effects on neuronal toxicity induced by Ab 1-42 and Ab [25][26][27][28][29][30][31][32][33][34][35] . It can completely reverse the toxic action induced by Ab 1-42 and partially by Ab [25][26][27][28][29][30][31][32][33][34][35] . These effects involve TrkB receptor activation since the effect is inhibited by K252a.…”
Section: Bdnf/trkb and Abmentioning
confidence: 99%
“…31 Septal neuron cultures treated with BDNF, IGF-1 or glial cell-derived neurotrophic factor (GDNF) or co-cultured with genetically modified human neural progenitor cells (hNPC) secreting these neurotrophic factors (but not allowing contact between the two cell types), were protected from oligomeric Ab 1-42 peptide-induced cell death. 30 Whether TrkB is involved in Ab production or aggregation in AD remains unknown. Further evidence for a role of TrkB in AD is that TrkB can modulate APP levels and proteolysis.…”
Section: Bdnf/trkb and Abmentioning
confidence: 99%
“…The role of BDNF is also well described in AD literature. Several studies have demonstrated the neuroprotective effect of BDNF in A␤ induced neurotoxicity in cultured neurons [50][51][52][53]. Enhanced BDNF expression was found to be protective against apoptotic cells in APP/PS1 double transgenic mouse model of AD [54].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro neurotoxicity studies have reported that oligomeric Aβ species are substantially more toxic (EC 50 ≤ 10 μM) to neuronal cortical cultures than either protofibrils or fibrils (EC 50 > 10 μM) (Ahmed et al, 2010;Kitiyanant et al, 2012;Dai et al, 2013). The underlying mechanism of Aβ oligomer toxicity to cortical neurons includes induction of Ca 2+ entry through NMDA and AMPA receptors, causing mitochondrial Ca 2+ overload, subsequent oxidative stress and mitochondrial membrane depolarization (Butterfield et al, 2007, Alberdi et al, 2010.…”
Section: Discussionmentioning
confidence: 99%